The role of hydroxychloroquine during the periconception period for recurrent miscarriage – a prospective observational study - Singh, Mamta; Tripura, Nani Gopal (International Journal Of Community Medicine And Public Health, 2025)
Background: Recurrent miscarriage (RM) remains a significant clinical challenge with multifactorial etiologies, many of which are immunological or unexplained. Hydroxychloroquine (HCQ), an antimalarial with immunomodulatory properties, has shown promise in improving pregnancy outcomes in autoimmune conditions. However, its role in RM, particularly during the periconception period, has not been extensively explored. Objective was to evaluate the safety and efficacy of hydroxychloroquine administered during the periconception period in women with a history of recurrent miscarriage. Methods: A prospective observational study was conducted on 160 women with a history of ≥3 miscarriages. Participants were administered 200 mg of HCQ daily for three months prior to attempting conception. Comprehensive clinical, hematological, and biochemical assessments were performed at baseline and during follow-up. Adverse events and pregnancy outcomes were recorded. Results: A total of 115 women (71.9%) conceived following periconception HCQ therapy. Among them, 45.2% had full-term normal vaginal deliveries, 26.1% underwent cesarean sections, and 15.7% experienced preterm deliveries, while 13.0% had first-trimester losses. Most participants (75%) were asymptomatic during therapy, with 12.5% reporting mild gastrointestinal symptoms and 6.25% experiencing transient hepatic enzyme elevations. Laboratory parameters remained stable, with no significant deterioration. HCQ was well-tolerated overall, and no new infections or seroconversions were observed. Conclusions: Periconception use of HCQ appears to be a safe and potentially effective therapeutic option in improving conception and pregnancy outcomes in women with recurrent miscarriage. Further randomised controlled trials are recommended to validate these findings.